Pengaruh Kinerja Pegawai Terhadap Efektivitas Organisasi Pada Kantor Kecamatan Dusun Selatan Kabupaten barito selatan: The Effect of Employee Performance on Organizational Effectiveness in the Kecamatan Dusun Selatan Office of Selatan Barito District - Nugraha, Muhammad Emil S (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2020)
This study aims to determine the Effect of Employee Performance on Organizational Effectiveness at the Dusun Selatan District Office, South Barito Regency in 2020. The theory used in this research is the performance in the organization which can be seen from the productivity, service quality, responsiveness, responsibility, employee accountability according to Agus Dwiyanto (2008: 50-51) and effectiveness which comes from the word effective, which is a job that is said to be effective if a job can produce one unit of output (output). A job is said to be effective if a job can be completed on time according to a predetermined plan, there are indicators that affect organizational effectiveness, there are several parts, namely goal achievement, integration, adaptation. According to Duncan quoted by Richard M. Steers (1985: 9) in Zulkarnain (2012: 42) This research uses quantitative methods with data collection techniques using observation, interviews, documentation and questionnaires. This research has two variables, namely independent variable (X) Devendent employee performance (Y) Organizational Effectiveness. The analytical tool used is simple regression using SPSS Version 25. The results obtained in the simple regression calculation are Y = 7.098 + 0.848 X where the value (a) is 7.098 and the coefficient value (b) is 0.848. Then the results of tcount from the above test show that tcount> table (6,538> 2,042) then Ho is rejected and Ha is accepted. This means that there is a significant influence between Employee Performance on Organizational Effectiveness at Dusun Selatan District Heads in South Barito Regency in 2020.